PEMANFAATAN PEWARNA ALAMI BUAH SENGGANI UNTUK BATIK TULIS MOTIF TANAMAN SENGGANI - Prasetyanti, Lucky Dwi; Santoso, RatnaEndah; Widiastuti, Theresia (TEXTURE Art and Culture Journal, 2024)
The background of working on this project is that the Senggani plant has a high availability compared to other shrubs.This plant has not used enough, so batik using natural dyes from the fruit Senggani needs to be developed. Senggani natural dye is used as a dye for hand-written batik. The development of visual processing of the motifs of Senggani plants with deformation styling.The material used is silk shiffon. The problem in this design is how to use Senggani fruit as a natural dye for hand-written batik for shawls, from these problems the resulting color and techniques are processed with attractive and maximum visual development.The process of creating works is adapted to several aspects of the design, namely aspects of function, aesthetic aspects,material aspects and aspects of the production process. These four aspects must be related to one another. The process of visualizing this design goes through several stages, namely design processing, color extraction, cloth memordan,mola,batik,coloring,colorfixation,nemboki and pelorodan.Based on the design process carried out, the results show that Senggani fruit can be used as an alternative to natural dyes for batik,and its shape can be used as inspiration for the batik motif itself.